2011
DOI: 10.4314/acsj.v18i4.68651
|View full text |Cite
|
Sign up to set email alerts
|

Detection and elimination of sweetpotato viruses

Abstract: In sub-Saharan Africa, sweetpotato (Impomoea batatas L.) production is greatly constrained by sweetpotato virus disease (SPVD) complex. This study was conducted to assess the incidence of viruses in healthy-looking sweetpotato in Uganda and to optimise modern technologies for virus diagnosis. A collection of healthy-looking sweetpotato vines from central Uganda were serologically assayed for sweetpotato viruses and the positive samples were confirmed by RT-PCR. A multiplex RT-PCR assay was optimised for simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…Lack of reversion by SPCSV-infected plants was also observed under field conditions (Adikini et al, 2016), which makes SPCSV a limiting factor in cleaning sweetpotato planting material; although in some cultivars, infected plants can easily be identified visually by symptoms. This agrees with the work of Rukarwa et al (2010), who did not obtain any virus-cleaned material from plants infected with SPCSV when subjected to meristem tip culture and thermotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lack of reversion by SPCSV-infected plants was also observed under field conditions (Adikini et al, 2016), which makes SPCSV a limiting factor in cleaning sweetpotato planting material; although in some cultivars, infected plants can easily be identified visually by symptoms. This agrees with the work of Rukarwa et al (2010), who did not obtain any virus-cleaned material from plants infected with SPCSV when subjected to meristem tip culture and thermotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with that of Gasura et al (2009), that cultivars with the ability to recover were common in the high-SPVD pressure zones in central and western regions of Uganda. Also, the reversion of most Ugandan cultivars from SPFMV infection makes it easier to clean infected plants through meristem tip culture and thermotherapy (Rukarwa et al, 2010). On the other hand, no cultivar reverted from SPCSV, although there was reduction in virus titer by the fifth month after sprouting.…”
Section: Discussionmentioning
confidence: 99%
“…Even though 52.4 % of sweet potato plants infected with the virus were cleaned through thermotherapymeristem tip culture, it is of great significance when the effect of virus on yield is considered. Rukarwa et al (2010) also reported that 77 % of virus-infected plants in Central Uganda were eliminated through meristem tip culture coupled with thermotherapy of 32 O C for four weeks, and this compares favourably with the result in this work.…”
Section: Thermotherapy Coupled With Meristem Culture To Eliminate Splcvsupporting
confidence: 80%
“…These results showed a greater scope than those exhibited in patchouli (Pogostemon cablin) (Noveriza et al, 2012) in which therapy did not eliminate the virus in any of the time treatments (10, 20, and 30 min) even when higher temperatures (50, 55, and 60 °C) than those of thermotherapy in the MSXJ hybrid were used. When these treatments are compared with those of Rukarwa et al (2010) using conventional thermotherapy (32 °C for 8 h in darkness and/or at 36 °C for 16 h light for 4 wk), it is possible to verify that they did not completely eliminate SPCSV even when thermotherapy was combined with meristem cultivation. Similarly, Bota et al (2014), in their experiment to obtain virus-free Vitis vinifera L. tissues, determined the low effectiveness of thermotherapy (20%) using a thermal chamber at 37.5/34.0 ºC (day/night) for 40 d.…”
Section: Thermotherapymentioning
confidence: 99%